Polio supplementary immunization campaign evaluation: the Maban experience, Upper Nile state, South Sudan, August 2013 - Amenu Wesen Denegetu (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2013)
The recent polio outbreak in Somalia, Kenya and Ethiopia demanded a safety net Sub-National Immunization Days (SNIDs) for four bordering States, including Upper Nile. Aiming to reach children aged 0-59 months, a house-to-house strategy was employed from 20-23 of August 2013 to vaccinate all children in Maban County. The post Campaign evaluation is conducted to assess coverage by finger mark (quality by proxy) and help to ensure improvements for subsequent campaigns. The main objective of the evaluation was to assess the quality of the campaign to learn lessons for subsequent plans.